Pendidikan dalam Keluarga Berbasis Fiqh Prioritas - Muhammad Shofi Mubarok (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Abstract: The problems facing mankind in the era of globalzation is very complex Therefore, people must have the right mindset. The wrong mindset wil not be able to solve the problem, but wil further add to the problem. Chidren from an early age to be prepared to have the right mindset to solve the problem. The considerations which will greatly help the children to be able to take quality decisions. As Muslims consideration based on the Qur’an and Sunnah, is a necessity in life. This way of thinking is based on the Qur’an and Sunnah then break dowm by the scholars of fiqh into usul fiqh rules, including the rules of fiqh of priorities Dedsion making is based on the rules of fiqh priority is divided into 3 groups of consideration (fiqh rules of priority), where in deciding child should be able to put the problem into proper group before deciding. First, consideration of the kindness parents should be able to teach, to give an example, convert the way of thinking and to assist children in applying the right mindset in preparation to face the problem. Keywords: Education at Home, Fiqh Priority.